(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Analysis of changes in brain matter (BM) according to the type of “leukoaraiosis” (LA) in patients depending on the presence of hypertensive crises (HC) in the anamnesis in order to reduce the risk of stroke.